Glass-ceramics, preparation method thereof and glass-ceramics products
Microcrystalline glass was prepared by two-step crystallization method to generate a mesh skeleton structure of Al4B2O9 and B2O3, which solved the problem of uneven distribution of components in microcrystalline glass, and significantly improved its mechanical properties and thermal shock resistance.
Patent Information
- Application Number
- CN202211441039.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-17
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2042-11-17
AI Technical Summary
In the prior art, the components in the microcrystalline glass are unevenly distributed, which affects its mechanical properties.
Microcrystalline glass is prepared by two-step crystallization method. First, it is insulated at 600°C to 700°C for 2 hours to 3 hours, and then at 750°C to 830°C for 1 hour to 2 hours, and Al4B2O9 is generated by the reaction between Al2O3 and B2O3. And form a network skeleton structure of B2O3.
The uniform distribution of each component in the microcrystalline glass is achieved, its mechanical properties and thermal shock resistance are improved, and the fracture toughness and fall resistance of the material are significantly improved.
Smart Images

Figure BDA0003948383820000081 
Figure BDA0003948383820000091
Abstract
Description
Technical Field
[0001] The present invention relates to the field of microcrystalline glass, and more specifically, to a microcrystalline glass, a method for preparing microcrystalline glass, and a microcrystalline glass product. Background Art
[0002] Glass-ceramics is a multiphase composite of a dense microcrystalline phase and a glass phase formed by crystallizing glass with specific components at a certain temperature so that a large number of tiny crystals are uniformly precipitated in the glass.
[0003] The atoms inside ordinary glass are arranged irregularly, which is one of the reasons why ordinary glass is fragile. However, microcrystalline glass has the dual characteristics of glass and ceramics. It is brighter than ceramics and tougher than glass. Specifically, microcrystalline glass is composed of crystals like ceramics, that is, the atoms inside microcrystalline glass are arranged regularly. Therefore, microcrystalline glass has stronger toughness than ordinary glass. Due to the excellent mechanical properties of microcrystalline glass, it is increasingly used in various fields.
[0004] Since microcrystalline glass has more complex components than ordinary glass, how to evenly distribute the components in the microcrystalline glass is crucial to improving the performance of the microcrystalline glass.
[0005] The above information disclosed in this Background section is only for enhancement of understanding of the background of the inventive concept and therefore the above information may contain information that does not form the prior art that is already known in this country to a person skilled in the art. Summary of the invention
[0006] In order to solve one or more of the problems existing in the prior art, the present invention provides a glass-ceramic, a method for preparing the glass-ceramic, and a glass-ceramic product.
[0007] An exemplary embodiment of the inventive concept provides a glass-ceramic, which is prepared from a base glass by a two-step crystallization method, wherein the base glass comprises, by weight: 15 to 25 parts of SiO2, 50 to 75 parts of B2O3, 5 to 10 parts of Al2O3, 0.1 to 0.2 parts of Li2O, 0 to 0.1 parts of K2O, 3 to 4 parts of TiO2, and 1 to 2 parts of ZrO2.
[0008] According to an exemplary embodiment of the present inventive concept, the glass-ceramics includes Al4B2O9 generated by reacting Al2O3 with B2O3.
[0009] According to an exemplary embodiment of the inventive concept, the glass-ceramic includes B 2 O 3 as a skeleton structure.
[0010] According to an exemplary embodiment of the present inventive concept, a mass ratio of SiO 2 to B 2 O 3 in the base glass is 1:2.4 to 1:3.75.
[0011] An exemplary embodiment of the present invention provides a method for preparing microcrystalline glass, the method comprising the following steps: preparing a base glass; preparing the base glass into the microcrystalline glass by a two-step crystallization method, wherein the base glass comprises, by weight: 15 to 25 parts of SiO2, 50 to 75 parts of B2O3, 5 to 10 parts of Al2O3, 0.1 to 0.2 parts of Li2O, 0 to 0.1 parts of K2O, 3 to 4 parts of TiO2, and 1 to 2 parts of ZrO2.
[0012] According to an exemplary embodiment of the present inventive concept, the glass-ceramics includes Al4B2O9 generated by reacting Al2O3 with B2O3.
[0013] According to an exemplary embodiment of the inventive concept, the glass-ceramic includes B 2 O 3 as a skeleton structure.
[0014] According to an exemplary embodiment of the present invention, in the two-step crystallization method, the first crystallization step includes: keeping the base glass at 600°C to 700°C for 2 to 3 hours; the second crystallization step includes: keeping the product obtained by the first crystallization at 750°C to 830°C for 1 to 2 hours.
[0015] According to an exemplary embodiment of the present inventive concept, a mass ratio of SiO 2 to B 2 O 3 in the base glass is 1:2.4 to 1:3.75.
[0016] Exemplary embodiments of the present inventive concept provide a glass-ceramic product including the above-mentioned glass-ceramic.
[0017] According to an exemplary embodiment of the present inventive concept, the glass-ceramic product is a glass-ceramic water cup. DETAILED DESCRIPTION
[0018] The exemplary embodiments according to the inventive concept will be described in detail below to explain the present invention. However, the present invention can be implemented in a variety of different forms and should not be construed as being limited to the exemplary embodiments proposed herein. These embodiments are provided so that the disclosure of the present invention will be thorough and complete, and the scope of the present invention will be fully conveyed to those skilled in the art.
[0019] The glass-ceramics according to the present inventive concept will be described in detail below.
[0020] Glass-ceramics are generally made from a base glass with specific components through a high-temperature crystallization method. The process for preparing the base glass includes the steps of mixing the various components and then melting them. In this step, if the viscosity of the molten glass is too large, it will affect the uniform distribution of the various components, resulting in uneven distribution of the various components in the final glass-ceramics, affecting the properties of the glass-ceramics (especially the mechanical properties).
[0021] The microcrystalline glass of the present invention is prepared from a base glass by a two-step crystallization method. That is, in the present invention, a base glass is first prepared, and then the base glass is prepared into microcrystalline glass by a two-step crystallization method.
[0022] In an exemplary embodiment of the present inventive concept, the base glass may include the following components by weight: 15 to 25 parts of SiO2, 50 to 75 parts of B2O3, 5 to 10 parts of Al2O3, 0.1 to 0.2 parts of Li2O, 0 to 0.1 parts of K2O, 3 to 4 parts of TiO2, and 1 to 2 parts of ZrO2. Among the above components, SiO2, B2O3 and Al2O3 can be used as the main materials of the base glass, Li2O and K2O can be used as fluxing agents, and TiO2 and ZrO2 can be used as nucleating agents.
[0023] During the preparation process of the two-step crystallization method, Al2O3 and B2O3 react to generate Al4B2O9. Therefore, in addition to the above-mentioned components in the base glass, the microcrystalline glass conceived by the present invention may also include Al4B2O9 generated by the reaction of Al2O3 and B2O3. It is understandable that during the preparation process of the two-step crystallization method, Al2O3 and B2O3 may not all participate in the reaction, and the microcrystalline glass conceived by the present invention may include unreacted Al2O3 and B2O3.
[0024] Since a two-step crystallization method is used for the preparation process, a large number of fine microcrystalline phases can exist in the microcrystalline glass conceived by the present invention. The microcrystalline phase has high hardness, neatly arranged atoms, and higher strength than the glass phase of the same component. Moreover, the microcrystalline phase is distributed in the microcrystalline glass, which can prevent the expansion of cracks, thereby improving the fracture toughness of the material. The microcrystalline glass conceived by the present invention has excellent mechanical properties.
[0025] In the two-step crystallization preparation process, Al4B2O9 generated by the reaction of Al2O3 and B2O3 exists in the form of whiskers, which have stable performance and excellent mechanical properties, and can improve the drop resistance of microcrystalline glass.
[0026] In addition, among the components of the base glass, the content of B2O3 is relatively high, so there will be a relatively large amount of B2O3 in the microcrystalline glass formed after the two-step crystallization method, and these B2O3 can form a network skeleton structure in the microcrystalline glass conceived by the present invention. Due to the network skeleton structure formed by B2O3, the microcrystalline glass conceived by the present invention can have excellent thermal shock resistance and can withstand rapid changes in temperature. For example, when the microcrystalline glass conceived by the present invention is subjected to rapid cooling and heating or is used in a microwave oven, it is not easy to break.
[0027] On the other hand, B2O3 can effectively reduce the viscosity of the glass material in a molten state. In an exemplary embodiment of the present invention, since the content of B2O3 in the base glass is relatively high, when the components of the base glass are prepared into a base glass product through a glass processing process, especially when the components are heated and melted to form a molten glass liquid, the relatively high content of B2O3 can effectively reduce the viscosity of the glass in a molten state, improve the fluidity of the components in the molten glass, and make the distribution of the components more uniform. Therefore, in the base glass of the present invention, the components can be distributed in a relatively uniform state.
[0028] In addition, since both crystallization methods need to be carried out at relatively high temperatures, B2O3 can also enhance the molecular mobility of each component during the two-step crystallization process, thereby further promoting a more uniform distribution of each component in the microcrystalline glass conceived by the present invention.
[0029] In an exemplary embodiment of the present inventive concept, in the base glass, the mass fraction of B 2 O 3 may be greater than 55%.
[0030] In an exemplary embodiment of the inventive concept, since a microcrystalline phase is generated in the base glass by a two-step crystallization method, how to promote the generation of the microcrystalline phase is also one of the technical problems to be solved by the inventive concept. The inventors have found through research that when the mass ratio of SiO2 to B2O3 in the base glass is in the range of 1:2.4 to 1:3.75, the crystallization activation energy in the crystallization process can be reduced to the greatest extent, which is conducive to the precipitation of crystals and increases the proportion of the microcrystalline phase in the microcrystalline glass. Therefore, in the base glass for preparing the microcrystalline glass of the inventive concept, the mass ratio of SiO2 to B2O3 is in the range of 1:2.4 to 1:3.75, preferably, in the range of 1:2.7 to 1:3.4, more preferably, in the range of 1:2.9 to 1:3.1, more preferably, the mass ratio of SiO2 to B2O3 is 1:3. When the mass ratio of SiO2 to B2O3 is within the above range, the proportion of the microcrystalline phase in the microcrystalline glass can be increased, so that the microcrystalline glass has better mechanical properties.
[0031] The microcrystalline glass conceived in the present invention has a network skeleton structure formed by B2O3, and the components therein are evenly distributed, so it has excellent thermal shock resistance and excellent mechanical properties.
[0032] Hereinafter, a method for preparing glass-ceramics according to the present inventive concept will be described.
[0033] The preparation method of the microcrystalline glass conceived by the present invention comprises the following steps: preparing a base glass; and preparing the base glass into the microcrystalline glass by a two-step crystallization method, wherein the base glass comprises, by weight: 15 to 25 parts of SiO2, 50 to 75 parts of B2O3, 5 to 10 parts of Al2O3, 0.1 to 0.2 parts of Li2O, 0 to 0.1 parts of K2O, 3 to 4 parts of TiO2, and 1 to 2 parts of ZrO2.
[0034] For example, 15 to 25 parts by weight of SiO2, 50 to 75 parts by weight of B2O3, 5 to 10 parts by weight of Al2O3, 0.1 to 0.2 parts by weight of Li2O, 0 to 0.1 parts by weight of K2O, 3 to 4 parts by weight of TiO2, and 1 to 2 parts by weight of ZrO2 are uniformly mixed to obtain a mixture, and then the mixture is formed into a base glass using a conventional glass forming process. The conventional glass forming process may include a step of heating and melting the mixture, in which the viscosity of the molten glass can be effectively reduced due to the high content of B2O3 in the mixture, so that each component is distributed more uniformly in the formed base glass.
[0035] In an exemplary embodiment of the present inventive concept, in the base glass, the mass fraction of B 2 O 3 may be greater than 55%.
[0036] Then, the base glass can be processed by a two-step crystallization method to generate a microcrystalline phase inside the base glass to obtain microcrystalline glass.
[0037] For example, the two-step crystallization method may include a first-step crystallization and a second-step crystallization.
[0038] In the first step of crystallization, the base glass can be heated to 600°C to 700°C at a rate of 1°C / min to 20°C / min and kept at this temperature for 2 to 3 hours. During this process, a chemical reaction 2Al2O3+B2O3→Al4B2O9 will occur inside the base glass, and the generated Al4B2O9 will begin to slowly crystallize and nucleate.
[0039] In the second step of crystallization, the base glass after the first step of crystallization can be heated to 750°C to 830°C at a rate of 1°C / min to 20°C / min and kept warm for 1 to 2 hours. In this process, the core inside the glass grows rapidly to generate Al4B2O9 whiskers, completing the overall crystallization process inside the glass.
[0040] If a one-step crystallization method is used, crystals will precipitate quickly at the interface inside the glass, thereby generating stress defects, making the glass more brittle, and even causing cracking problems. The preparation method of the microcrystalline glass conceived by the present invention adopts a two-step crystallization method. In the first step of crystallization, the crystal phase mainly composed of Al4B2O9 is first nucleated at a temperature 50°C to 100°C lower than the crystallization temperature. Then, in the second step of crystallization, the crystal phase mainly composed of Al4B2O9 is further fully crystallized to form Al4B2O9 whiskers. The two-step crystallization process of step-by-step nucleation and then growth can reduce stress defects in the glass. At the same time, since the process of whisker formation is relatively slow, the two-step crystallization method can also help form whiskers, thereby improving the mechanical properties of the microcrystalline glass.
[0041] In addition, during the two-step crystallization process, due to the high B2O3 content in the glass, it can help to enhance the molecular mobility of each component, thereby further promoting the distribution of each component in the microcrystalline glass in a more uniform state.
[0042] On the other hand, in the glass-ceramics formed after the two-step crystallization method, there is also a relatively high content of B2O3, which can form a network skeleton structure in the glass-ceramics. Due to the network skeleton structure formed by B2O3, the glass-ceramics conceived by the present invention can have excellent thermal shock resistance and can withstand rapid changes in temperature. For example, when the glass-ceramics conceived by the present invention is subjected to rapid cooling and heating or is used in a microwave oven, it is not easy to break.
[0043] By using the method for preparing glass-ceramics conceived by the present invention, stress defects in glass-ceramics can be reduced to form dense and uniform Al4B2O9 whiskers. In addition, the components in the prepared glass-ceramics are evenly distributed, and the glass-ceramics have a mesh skeleton structure formed by B2O3. Therefore, the glass-ceramics prepared by the method for preparing glass-ceramics conceived by the present invention have excellent thermal shock resistance and mechanical properties.
[0044] In addition, the present invention also provides a glass-ceramic product, which may be a water cup, but is not limited thereto. The glass-ceramic product includes the above-mentioned glass-ceramic or includes the glass-ceramic prepared by the above-mentioned method.
[0045] The following will describe the method for preparing glass-ceramics according to the present invention in conjunction with specific embodiments.
[0046] Example 1
[0047] A glass material mixture was prepared, the glass material mixture including, by weight, 20 parts of SiO2, 60 parts of B2O3, 7.5 parts of Al2O3, 0.15 parts of Li2O, 0.05 parts of K2O, 3.5 parts of TiO2, and 1.5 parts of ZrO2.
[0048] The glass material mixture is prepared into a water cup formed of basic glass through a conventional glass forming process. For example, the conventional glass forming process includes: weighing the powder of the glass material in proportion and mixing it evenly; melting it into glass liquid at a high temperature of 1700°C in a glass melting furnace; injecting the glass liquid into a mold, and using the mold to stamp and form it into a glass water cup.
[0049] In the first step of crystallization, the glass water cup was heated to 650°C at a rate of 10°C / min and kept at this temperature for 2.5 hours.
[0050] In the second step of crystallization, the glass water cup that has been crystallized in the first step is heated to 790° C. at a rate of 10° C. / min and kept at this temperature for 1.5 hours.
[0051] After the above steps, the microcrystalline glass water cup of Example 1 is obtained.
[0052] Example 2
[0053] The difference from Example 1 is that the weight proportion of SiO2 is 15 parts and the weight proportion of B2O3 is 55 parts.
[0054] Example 3
[0055] The difference from Example 1 is that the weight portion of SiO2 is 25 parts.
[0056] Example 4
[0057] The difference from Example 1 is that the weight portion of B2O3 is 50 parts.
[0058] Example 5
[0059] The difference from Example 1 is that the weight proportion of B2O3 is 75 parts.
[0060] Example 6
[0061] The difference from Example 1 is that the weight portion of Al2O3 is 5 parts.
[0062] Example 7
[0063] The difference from Example 1 is that the weight portion of Al2O3 is 10 parts.
[0064] Example 8
[0065] The difference from Example 1 is that the weight portion of Li2O is 0.1 part.
[0066] Example 9
[0067] The difference from Example 1 is that the weight portion of Li2O is 0.2 parts.
[0068] Example 10
[0069] The difference from Example 1 is that K2O is not contained.
[0070] Embodiment 11
[0071] The difference from Example 1 is that the weight portion of K2O is 0.1 part.
[0072] Example 12
[0073] The difference from Example 1 is that the weight portion of TiO2 is 3 parts.
[0074] Example 13
[0075] The difference from Example 1 is that the weight portion of TiO2 is 4 parts.
[0076] Embodiment 14
[0077] The difference from Example 1 is that the weight portion of ZrO2 is 1 part.
[0078] Embodiment 15
[0079] The difference from Example 1 is that the weight portion of ZrO2 is 2 parts.
[0080] Example 16
[0081] The difference from Example 1 is that in the first crystallization step, the base glass is heated to 600°C.
[0082] Embodiment 17
[0083] The difference from Example 1 is that in the first crystallization step, the base glass is heated to 700°C.
[0084] Embodiment 18
[0085] The difference from Example 1 is that in the second crystallization step, the base glass is heated to 750°C.
[0086] Embodiment 19
[0087] The difference from Example 1 is that in the second crystallization step, the base glass is heated to 830°C.
[0088] Embodiment 20
[0089] The difference from Example 1 is that in the first crystallization step, the base glass is heated to 650° C. and then kept at this temperature for 2 hours.
[0090] Embodiment 21
[0091] The difference from Example 1 is that in the first crystallization step, the base glass is heated to 650° C. and then kept at this temperature for 3 hours.
[0092] Embodiment 22
[0093] The difference from Example 1 is that in the second crystallization step, the base glass is heated to 790° C. and then kept at this temperature for 1 hour.
[0094] Embodiment 23
[0095] The difference from Example 1 is that in the second crystallization step, the base glass is heated to 790° C. and then kept at this temperature for 2 hours.
[0096] Comparative Example 1
[0097] The difference from Example 1 is that the weight proportion of SiO2 is 7 parts and the weight proportion of B2O3 is 21 parts.
[0098] Comparative Example 2
[0099] The difference from Example 1 is that the weight proportion of SiO2 is 40 parts and the weight proportion of B2O3 is 80 parts.
[0100] Comparative Example 3
[0101] The difference from Example 1 is that the weight parts of SiO2 are 8 parts and the weight parts of B2O3 are 32 parts.
[0102] The microcrystalline glass cups prepared in the above-mentioned Examples 1 to 23 and Comparative Examples 1 to 3 were subjected to thermal shock resistance test, impact height test and impact strength test. The specific test standards are as follows:
[0103] Thermal shock resistance test
[0104] The glass-ceramic water cups prepared in Examples 1 to 23 were placed in a high-temperature furnace at 440°C to 460°C for 5 minutes, and then taken out and placed in water at 15°C to 25°C for cooling. The above steps were repeated until the glass-ceramic water cups had cracks or other abnormalities, and the number of repetitions was recorded.
[0105] Impact height and impact strength testing
[0106] The test was carried out in accordance with GB / T 39814-2021 "Ultra-thin glass impact strength test method-dropping ball impact method", and a 32±0.5g steel ball with a diameter of 19.811mm was used to test its impact height and impact strength.
[0107] Table 1
[0108]
[0109]
[0110] It can be seen from the data in Table 1 that the glass-ceramic water cups prepared according to the embodiments of the present invention all have good thermal shock resistance, impact height and impact strength.
[0111] It can be seen from Examples 1 to 5 that when the ratio of SiO2 to B2O3 is in the range of 1:2.4 to 1:3.75, the microcrystalline glass water cups all have good mechanical properties. In contrast, the mechanical properties of the microcrystalline glass water cups of Comparative Examples 2 and 3 are significantly reduced. This is because, when the ratio of SiO2 to B2O3 is not within the above range, the crystallization activation energy during the crystallization process cannot be reduced or is not significantly reduced, so the proportion of microcrystalline phase in the microcrystalline glass water cup is not high, which makes the mechanical properties of the microcrystalline glass water cups of Comparative Examples 2 and 3 lower than those of the embodiments.
[0112] In addition, it can be seen from Examples 6 to 15 that, when the ratio of SiO2 to B2O3 is maintained at 1:3 and the content of B2O3 is substantially higher than 60%, the content of other components has little effect on the thermal shock resistance and mechanical properties of the microcrystalline water cup.
[0113] It can be seen from Examples 16 to 23 that, while maintaining the ratio of SiO2 to B2O3 at 1:3 and the content of B2O3 being substantially higher than 60%, a two-step crystallization method is adopted, and the temperature and time of the above-mentioned crystallization process are ensured, the microcrystalline glass water cup can have good thermal shock resistance and mechanical properties.
[0114] The B2O3 content in the glass material mixture of Comparative Example 1 is low, so during the basic glass forming and crystallization process, the fluidity of each component cannot be effectively improved, the component distribution is less uniform than that of the embodiment, and the B2O3 content as the skeleton structure is low, so its thermal shock resistance is poor.
[0115] The above description is only a preferred embodiment of the present invention and is not intended to limit the scope of implementation of the present invention. If the present invention is modified or replaced by equivalents without departing from the spirit and scope of the present invention, it should be included in the protection scope of the claims of the present invention.
Claims
1. A glass-ceramic, characterized in that: The microcrystalline glass is prepared from a base glass by a two-step crystallization method, wherein the base glass comprises, by weight: 15-25 parts of SiO2, 50-75 parts of B2O3, 5-10 parts of Al2O3, 0.1-0.2 parts of Li2O, 0-0.1 parts of K2O, 3-4 parts of TiO2, and 1-2 parts of ZrO2. Among them, in the base glass, the mass fraction of B2O3 is greater than 55%. Wherein, the microcrystalline glass includes B2O3 as a skeleton structure, Wherein, the microcrystalline glass comprises Al4B2O9 generated by the reaction of Al2O3 and B2O3, and Wherein, the mass ratio of SiO2 to B2O3 in the base glass is 1:2.4 to 1:3.
75.
2. A method for preparing glass-ceramics, characterized in that: The method comprises the following steps: preparing base glass; The base glass is prepared into the glass-ceramics by a two-step crystallization method. The base glass comprises, by weight: 15-25 parts of SiO2, 50-75 parts of B2O3, 5-10 parts of Al2O3, 0.1-0.2 parts of Li2O, 0-0.1 parts of K2O, 3-4 parts of TiO2, and 1-2 parts of ZrO2. Among them, in the base glass, the mass fraction of B2O3 is greater than 55%. Wherein, the microcrystalline glass includes B2O3 as a skeleton structure, Wherein, the microcrystalline glass comprises Al4B2O9 generated by the reaction of Al2O3 and B2O3, and Wherein, the mass ratio of SiO2 to B2O3 in the base glass is 1:2.4 to 1:3.
75.
3. The method according to claim 2, characterized in that In the two-step crystallization method, The first step of crystallization includes: keeping the base glass at 600° C. to 700° C. for 2 to 3 hours; The second step of crystallization includes: keeping the product obtained by the first step of crystallization at 750° C. to 830° C. for 1 hour to 2 hours.
4. A glass-ceramic product, characterized in that: The microcrystalline glass product comprises the microcrystalline glass of claim 1.
5. The glass-ceramic product according to claim 4, characterized in that: The microcrystalline glass product is a microcrystalline glass water cup.